Characterization of sporotrichosis cases treated in a dermatologic teaching unit in the state of São Paulo - Brazil, 2003 - 2013 - Gabriela Franco Marques; Ana Luiza Grizzo Peres Martins; Juliana Martins Prazeres Sousa; Letícia Stella Gardini Brandão; Patrick Alexander Wachholz; Paula Yoshiko Masuda (Sociedade Brasileira de Dermatologia, 2015)
We conducted a transversal retrospective study with secondary data collection from 25 cases of sporotrichosis, treated at a teaching unit in inner São Paulo (Brazil), between the years 2003-2013. We found that the prevalence was higher in men (72%), rural workers (44%) and those living in rural areas (60%), with an average age of 42.48 years. The median between the onset of lesions and diagnosis was six weeks. Lesions predominated in the upper limbs (92%), and were classified as lymphocutaneous (80%) and fixed cutaneous (20%) forms. Clinical cure was observed in 62.5% of the cases treated with potassium iodide and 100% of cases treated with itraconazole.